Effect of suckling type and PUFA use on productive performances, quanti-qualitative characteristics of meat and fatty acid profile in lamb - Toteda, F.; Facciolongo, F.; Ragni et al., F. (Progress in Nutrition, 2011)
SummaryIn March, 24 male lambs were divided into three groups and fed as follows: maternal milk (MM); acidified milk replacer (MR); acidified milk replacer with 5% of the fat total amount replaced by a linseed and fish oil mixture (MR+PUFA). Milk consumption and live weight were recorded weekly. At slaughter we recorded the carcass composition, pH, tenderness, colorimetric characteristics, chemical and fatty acid composition of the meat. Natural suckling resulted in a better slaughter yield (P < 0.01), fatter carcasses, and meat which was more tender (P < 0.01), less bright (P < 0.01) and redder (P < 0.05) than the two experimental groups. Meat from naturally suckled lambs contained higher (P < 0.01) concentrations of saturated fatty acids (SFA) than the other groups. Samples from the MR+PUFA group showed higher (P < 0.01) levels of PUFA and a better PUFA/SFA ratio. The groups reared artificially showed atherogenicity and the thrombogenicity index lower (P < 0.01) than the group naturally feeding.Influenza del tipo di allattamento e dell’uso dei PUFA sulle performance produttive, sulle caratteristiche quanti-qualitative e sul profilo acidico della carne di agnelloRiassuntoNel mese di marzo, 24 agnelli sono stati divisi in tre gruppi e alimentati come segue: a) latte materno (MM); b) sostituto del latte acidificato (MR); c) sostituto del latte acidificato con sostituzione del 5% dei lipidi totali con una miscela di olio di lino e di pesce ricca in PUFA (MR + PUFA). L’allattamento naturale condiziona una migliore resa alla macellazione (P < 0.01), carcasse più grasse e carne significativamente (P < 0.01) più tenera (P < 0.01), meno luminosa e più rossa (P < 0,05). La carne degli agnelli allattati naturalmente evidenzia una maggiore concentrazione di acidi grassi saturi (SFA) mentre quella dei soggetti appartenenti al gruppo MR+PUFA risulta più ricca (P < 0.01) di acidi grassi polinsaturi (PUFA) e presenta un rapporto PUFA/SFA significativamente più elevato. L’allattamento artificiale ha determinato indici di aterogenicità e di trombogenicità marcatamente più bassi (P < 0.01).